The DNA adenine methylase of Salmonella Enteritidis promotes their intracellular replication by inhibiting arachidonic acid metabolism pathway in macrophages - Wang, Ming; Xiong, Dan; Wang, Xinwei; Gu, Dan; Meng, Chuang; Jiao, Xinan; Pan, Zhiming (Frontiers in Microbiology, 2023)
Macrophages can participate in immune responses by altering their metabolism, and play important roles in controlling bacterial infections. However, Salmonella Enteritidis can survive and proliferate in macrophages. After the deletion of DNA adenine methylase (Dam), the proliferation of Salmonella Enteritidis in macrophages decreased, the molecular mechanism is still unclear. After infecting macrophages with Salmonella Enteritidis wild type and dam gene deletion strains, intracellular metabolites were extracted and detected by non-targeted metabolomics and fatty acid targeted metabolomics. We found Dam had significant effects on arachidonic acid and related metabolic pathways in macrophages. The dam gene can promote the proliferation of Salmonella Enteritidis in macrophages by inhibiting the metabolic pathway of cytosolic phospholipase A2-mediated arachidonic acid production and conversion to prostaglandin E2 in macrophages, reducing the secretion of the pro-inflammatory factors IL-1β and IL-6. In addition, inhibition of arachidonic acid-related pathways in macrophages by Arachidonyl trifluoromethyl ketone could restore the proliferation of dam gene deletion strains in macrophages. This study explored the role of Dam in the process of Salmonella Enteritidis invading host cells from the perspective of host cell metabolism, and provides new insights into the immune escape mechanism of Salmonella Enteritidis.